Dess–Martin Periodinane/Brønsted Acid-Mediated Tandem Oxidation/Cyclization of Homopropargylic Alcohols for Synthesis of Trisubstituted Furans - Murakami, Miki; Miyazaki, Megumi; Ishibashi, Mayo; Oda, Mizuki; Takekuma, Karin; Horino, Yoshikazu (Synlett, 2023)
A facile, efficient, and metal-free single-flask procedure for the synthesis of trisubstituted furans from simple readily available homopropargylic alcohols is described. A combination of Dess–Martin periodinane, H2O, and TsOH·H2O plays a crucial role in the formation of the trisubstituted furans. The advantages of this method include operational ease, mild reaction conditions, and good functional-group tolerance.
Keywords: furans; Dess–Martin oxidation; 5-endo-dig cyclization; Brønsted acids; homopropargylic alcohols